Eco-friendly green tea waste dishwash / Sarvin Kanth Rajini Kanth, Suriya Selvam and Prheethikha Saravanan - Rajini Kanth, Sarvin Kanth; Selvam, Suriya; Saravanan, Prheethikha (2020)
Tea wastes are largely disposed into the environment without any treatment after tea preparation. Therefore, tea wastes have raised environmental pollution causing environmental degradation. This study proposed to recycle tea waste to better utilize the organic substance and also reduce environmental issues concerning to tea waste. Our study also investigated the various dishwashers in the market and found that commercial dishwashers are high in chemical substance and harmful to human skin. Our scope of study is to recycle household tea waste and to innovate into a natural dishwasher which is “Eco-Friendly Green Tea Waste Dishwash”. The objective of study is to minimalize the amount of tea waste released in the environment. Many samples are formulated with different proportions of green tea waste, coconut oil, salt and water. The samples are tested based on the liquid texture and effectiveness cleaning the greasy surfaces by respondents. The findings concluded that Eco-Friendly Green Tea Waste Dishwash is a unique formulation from natural ingredients which is suitable for sensitive and dry skin types. The Eco-Friendly Green Tea Waste Dishwash is a bio-degradable and environmental-friendly product. In conclusion, tea wastes are utilized effectively in order to reduce the impact of environmental pollution.